Pervasive Advertising - Müller, Jörg; Alt, Florian; Michelis, Daniel (Human-Computer Interaction Series, 2011)
Following decades of exciting developments in laboratories around the world, pervasive computing technologies are starting to reshape our world in real ways. Computers, visible and invisible, are everywhere: traditional signs and billboards are being replaced by digital signage, projections, and interactive surfaces. Communication is digital and ubiquitous-the majority of the world's population uses mobile phones. Physical computing and robotics make physical environments digital and interactive. It is apparent that analogous for developments on the Internet, advertising will be the business model driving pervasive computing. These new computing technologies are powerful tools for advertising and they will supersede traditional advertising in the near future. Pervasive computing is the disruptive technology for advertising. This book presents the core principles of Pervasive Advertising and makes accessible to practitioners and researchers alike research findings in pervasive computing, modern advertising, and human-computer interaction. The major opportunities addressed include: symmetric communication, the long tail, powerful experiences, personalization, context adaptivity, audience measurement, and automated persuasion. The major challenges addressed include: calm and engaging advertising, privacy, and ethical persuasion. This book presents and discusses innovative applications based on digital signage and mobile advertising, venturing into new territories like music and scents. This book is intended as a guide for: • Advertisers who want to understand how new technologies revolutionize their field. • Pervasive computing engineers and researchers who want to understand what business models will drive their technologies in the real world. • Anyone who is interested in how pervasive advertising will shape the future of urban life.